Eye Movements in Parkinson’s Disease and Inherited Parkinsonian Syndromes - Pretegiani, Elena; Optican, Lance M. (Frontiers in Neurology, 2017)
Despite extensive research, the functions of the basal ganglia (BG) in movement control have not been fully understood. Eye movements, particularly saccades, are convenient indicators of BG function. Here, we review the main oculomotor findings reported in Parkinson’s disease (PD) and genetic parkinsonian syndromes. PD is a progressive, neurodegenerative disorder caused by dopaminergic cell loss within the substantia nigra pars compacta, resulting in depletion of striatal dopamine and subsequent increased inhibitory BG output from the internal globus pallidus and the substantia nigra pars reticulata. Eye movement abnormalities are common in PD: anomalies are more evident in voluntary than reflexive saccades in the initial stages, but visually guided saccades may also be involved at later stages. Saccadic hypometria (including abnormally fragmented saccades), reduced accuracy, and increased latency are among the most prominent deficits. PD patients show also unusually frequent and large square wave jerks and impaired inhibition of reflexive saccades when voluntary mirror saccades are required. Poor convergence ability and altered pursuit are common. Inherited parkinsonisms are a heterogeneous group of rare syndromes due to gene mutations causing symptoms resembling those of PD. Eye movement characteristics of some parkinsonisms have been studied. While sharing some PD features, each syndrome has a distinctive profile that could contribute to better define the clinical phenotype of parkinsonian disorders. Moreover, because the pathogenesis and the underlying neural circuit failure of inherited parkinsonisms are often well defined, they might offer a better prospect than idiopathic PD to understand the BG function.